Pemanfaatan Chatgpt Dalam Pembelajaran Persamaan Dasar Akuntansi - Rahaningsih, Nining; Suarna, Nana; Dienwati Nuris, Nisa; Ade Kurnia, Dian; Rasyid, Abdul; Frihandiansah, Riyandi (TEMATIK, 2023)
Learning Accounting is an essential part of business and finance education. To ensure effective learning, an innovative approach is needed to optimize the understanding of concepts and practical applications in the field of accounting. One technology that has attracted attention in this context is Artificial Intelligence, particularly through the utilization of ChatGPT. However, there are still challenges in teaching accounting. Conventional learning systems are often less interactive and cannot provide adequate individual support to students. Therefore, a new approach is needed to enhance student interaction with instructors. The aim of this research is to analyze and implement the utilization of ChatGPT in the development of accounting educati to improve the understanding of accounting concepts and enhance students' ability to apply accounting knowledge. The research method employs an experimental approach involving a group of students in a learning program utilizing ChatGPT as a virtual assistant. ChatGPT provides explanations, answers questions, and provides feedback to students. To analyze and evaluate the effectiveness of using AI (ChatGPT) in accounting education, the System Usability Scale is used.The results of this research indicate that the use of AI, particularly through ChatGPT, in accounting education can provide significant benefits. Students experience improvements in their understanding of accounting concepts, practical abilities, better individual support, and increased motivation and interest in learning accounting, with an accuracy rate of 80.625%.